(untitled) (Global Journal of Computer Science and Technology, 2023)
Currently image transfer and storage require compression to reduce memory usage and to increase transmission speed In this article the hybrid compression algorithm is used for color black and white images It includes the discrete wavelet transform and the Walsh transform are used for quantization The Walsh transform coefficients are quantized and arithmetically encoded The combined output is compressed and can be transmitted over any available network in the shortest time The compressed image is decoded and the original image is decompressed using the inverse conversion operation